STUDIES ON CHLOROPLAST DEVELOPMENT AND REPLICATION IN EUGLENA : I. Vitamin B(12) and Chloroplast Replication - Carell, Edgar F. (The Rockefeller University Press, 1969)
When Euglena gracilis is grown under vitamin B(12) deficiency conditions, the amount of protein and of chlorophyll per cell increase with decrease of B(12) in the medium and consequently in the cell. The increase in cell protein is proportional to and precedes an increase in the number of chloroplasts per cell. This replication of the chloroplasts under deficiency conditions is not accompanied by nuclear or cell division. It is concluded that chloroplast replication in Euglena gracilis is independent of nuclear and cellular replication, at least under B(12) deficiency conditions. We established a graph of the growth of Euglena under different concentrations of vitamin B(12) added to the growth medium, which permitted us to calculate that at least 22,000 molecules of vitamin B(12) per cell are required to give normal growth.